Tool selection in South African integrated environmental management : comparing cost benefit analysis and simple multi-attribute ranking technique in terms of sustainability-thinking principles - Gale, Warren (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.